Analysis Of The Influence Of Technology, Education, And Social Support Factors On Improving The Quality Of Generation Z Human Resources In Mataram City - Meiza Ariya Budiarte; Irwan Cahyadi; Ega Dwi Putri (Business Management, 2026)
Technological development, education, and social support are considered important factors in improving the quality of human resources (HR), particularly among Generation Z, who have grown up in the digital era. This study aims to analyze the effects of technological development, education, and social support on the quality of human resources among Generation Z in Mataram City. This study employed a quantitative, associative research design. The sample consisted of 100 respondents selected using the Slovin formula and a simple random sampling technique. Data were analyzed using instrument testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The results indicate that, partially, technological development has a positive and significant effect on the quality of human resources (t = 6.214; sig. = 0.000 < 0.05), education has no significant effect (t = -1.736; sig. = 0.086 > 0.05), while social support has a positive and significant effect on the quality of human resources (t = 3.281; sig. = 0.001 < 0.05). Simultaneously, technological development, education, and social support have a significant effect on the quality of human resources (F = 16.477; sig. = 0.000 < 0.05). The Adjusted R Square value of 0.319 indicates that these three variables explain 31.9% of the variation in the quality of human resources. This study concludes that technological development and social support play significant roles in improving the quality of human resources among Generation Z in Mataram City, whereas education does not have a significant effect.